Oral enzymatic detoxification system: Insights obtained from proteome analysis to understand its potential impact on aroma metabolization. Issue 6 (15th October 2021) - Schwartz, Mathieu; Neiers, Fabrice; Charles, Jean‐Philippe; Heydel, Jean‐Marie; Muñoz‐González, Carolina; Feron, Gilles; Canon, Francis
Abstract: The oral cavity is an entry path into the body, enabling the intake of nutrients but also leading to the ingestion of harmful substances. Thus, saliva and oral tissues contain enzyme systems that enable the early neutralization of xenobiotics as soon as they enter the body. Based on recently published oral proteomic data from several research groups, this review identifies and compiles the primary detoxification enzymes (also known as xenobiotic‐metabolizing enzymes) present in saliva and the oral epithelium. The functions and the metabolic activity of these enzymes are presented. Then, the activity of these enzymes in saliva, which is an extracellular fluid, is discussed with regard to the salivary parameters. The next part of the review presents research evidencing oral metabolization of aroma compounds and the putative involved enzymes. The last part discusses the potential role of these enzymatic reactions on the perception of aroma compounds in light of recent pieces of evidence of in vivo oral metabolization of aroma compounds affecting their release in mouth and their perception. Thus, this review highlights different enzymes appearing as relevant to explain aroma metabolism in the oral cavity. It also points out that further works are needed to unravel the effect of the oral enzymatic detoxification system on the perception of food flavor in the context of the consumption of complex food matrices, while considering the impact of food oral processing. Thus, it constitutes a basis to explore these biochemical mechanisms and their impact on flavor perception.